The Influence of Lifestyle and Economic Instability on Debt Behavior in Pekalongan Regency - Marsa Retno Setifani; Hendri Hermawan Adinugraha (Yayasan Adra Karima Hubbi, 2024)
Debt is defined as money loaned from others with an obligation to repay. Debt management is an important aspect of personal finance that can be influenced by various factors, including consumptive lifestyles and economic instability. This literature review aims to understand the relationship between lifestyle, economic instability, and individual debt management behavior. A qualitative approach was used in this study to explore the phenomenon of debt behavior in the context of lifestyle and economic instability in Pekalongan Regency. Data was obtained from the Pekalongan Central Bureau of Statistics (BPS), participatory observation, document analysis, and in-depth interviews with Pekalongan residents who have experience in debt and related financial institutions. Data analysis was conducted qualitatively using the interaction analysis method to reveal the relationship between lifestyle, economic instability, and debt behavior in Pekalongan Regency. The results of this study are expected to provide a deeper understanding of the factors that influence debt management behavior and serve as a basis for developing effective strategies for managing debt wisely and responsibly.